Two-weighted inequality for parabolic sublinear operators in Lebesgue spaces - Mushtagov, F. M. (Methods of Functional Analysis and Topology, 2006)
In this paper, the author establishes the boundedness in weighted L_p spaces on R^n+1 with a parabolic metric for a large class of sublinear operators generated by parabolic Calderon-Zygmund kernels. The conditions of these theorems are satisfied by many important operators in analysis. Sufficient conditions on weighted functions ω and ω_1 are given so that certain parabolic sublinear operator is bounded from the weighted Lebesgue spaces L_p,ω(R^n+1) into L_p,ω_1(R^n+1).